Impact of climate change on palm oil production - Mohamad Zainalabidin, Syahaneem; Abdul Rahim, Khalid (School of Social Sciences, Universiti Sains Malaysia, 2012)
Agriculture plays a significant role in the resource-based socio economic development in Malaysia. Despite technological advances and improvements, climate is still the most important aspect in ensuring the continuous production of the agricultural sector. Agricultural sector had been found to be affected by the change in climate due to its vulnerability. Past studies had revealed that climate change has resulted in the decline of palm oil production. For example, in southern Malaysia, the production of crude palm oil has reduced to 1.1 million metric ton in 2006. Although there has been a significant amount of research and studies related to climate change and agriculture in Malaysia, there continues to be wide range of opinions regarding scenarios of the future impact especially on palm oil production. This paper will present the research proposal in assessing the impacts of climate change on agriculture sector, especially the palm oil production and propose important insights in managing the resources for the future.